2020
DOI: 10.1371/journal.pone.0234403
|View full text |Cite
|
Sign up to set email alerts
|

CPPED1-targeting microRNA-371a-5p expression in human placenta associates with spontaneous delivery

Abstract: MicroRNAs (miRNAs) are important regulators of gene expression, and their expression is associated with many physiological conditions. Here, we investigated potential associations between expression levels of miRNAs in human placenta and the onset of spontaneous term birth. Using RNA sequencing, we identified 54 miRNAs differentially expressed during spontaneous term labor compared to elective term births. Expression levels of 23 miRNAs were upregulated, whereas 31 were downregulated at least 1.5-fold. The upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, it was found via bioinformatics analysis in our research that there existed binding relationship between SP1 and another molecule calcineurin‐like phosphoesterase domain containing 1 (CPPED1). CPPED1 is a member of calcineurin‐like metallophosphoesterase superfamily involving in the timing of birth and spontaneous delivery 13,14 . It was disclosed that CPPED1 might be associated with the pathogenesis of osteonecrosis of the femoral head 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it was found via bioinformatics analysis in our research that there existed binding relationship between SP1 and another molecule calcineurin‐like phosphoesterase domain containing 1 (CPPED1). CPPED1 is a member of calcineurin‐like metallophosphoesterase superfamily involving in the timing of birth and spontaneous delivery 13,14 . It was disclosed that CPPED1 might be associated with the pathogenesis of osteonecrosis of the femoral head 15 .…”
Section: Introductionmentioning
confidence: 99%
“…CPPED1 is a member of calcineurin-like metallophosphoesterase superfamily involving in the timing of birth and spontaneous delivery. 13,14 It was disclosed that CPPED1 might be associated with the pathogenesis of osteonecrosis of the femoral head. 15 Even though the impact of CPPED1 in restenosis after PCI has barely been discussed before, it was known from the microarray data in our study that CPPED1 and SP1 were both highly expressed in the serum of patients with restenosis.…”
mentioning
confidence: 99%
“…Liang et al [ 127 ] analyzed the expression levels of 345 miRNAs in 40 normal tissues and found miR-30e-5p, miR-92a-3p, and miR-423-3p to have the least variable expression. Although our study has identified promising reference genes that can be universally used in different tissues, literature analysis has demonstrated that miRNA-16-5p, miRNA-103a-3p, and miRNA-191-5p are most commonly used as universal reference genes [ 29 , 31 , 35 , 42 , 89 , 99 , 110 ].…”
Section: Discussionmentioning
confidence: 99%